Understanding the fishery dynamics and stock health of mahi-mahi Coryphaena hippurus (Linnaeus, 1758) from Indian coastal waters: Stock status of Mahi-mahi - E. M. Abdussamad,; S. Surya,; A. Margaret Muthu Rathinam,; K. G. Mini,; K. M. Rajesh,; P. Abdul Azeez,; T. B. Ratheesh,; S. Febna ,; N. V. Dipti, (Indian Journal of Fisheries, 2024)
This work delves into the mahi-mahi (dolphinfish) fishery along the Indian coast, noting itsdevelopmental stage precluding a full assessment. The analysis of population characteristicshighlights their inherent resilience, driven by early maturity, substantial fecundity and rapidgrowth rates. These traits collectively mitigate susceptibility to fishing pressure, ensuringthe maintenance of sizable spawning stock biomasses and recruitment. Through Kobeanalysis, it is determined that the present fishing mortality and biomass levels remain withinsafe thresholds, indicating absence of overfishing. However, regular monitoring is imperativeto swiftly implement management measures if necessary, safeguarding the sustainability ofthe mahi-mahi fishery in the long term.Keywords:Kobe plot, Population characteristics, Recruitment,Resilience, Spawning stock biomass